(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
A field trial was conducted at Shambat Research Station FarmKhartoum, Sudan during 2011/2012 and 2012/ 2013 winter seasons, toevaluate the activity and selectivity of the herbicide Clethodim (Selectsuper120 EC ) for weed control in alfalfa. The herbicide was tested at0.036, 0.048 and 0.060 kg a.i. /fed, as post- emergence treatments, 3weeks after sowing of alfalfa. The most prevailing weed species weresweet signal grass Brachiaria eruciformis (Sm) Grieseb., purple nutsedege (Cyperus rotundus L.) and croton Chrozophora plicata (Vahl.)A. Juss. Exspreng. Results showed that the losses due to competition indry matter yield of alfalfa were 57% and 37% in the first cut, in the firstand second seasons, respectively. All herbicide treatments were highlyselective to the crop. The herbicide at all rates tested gave consistent andeffective control of grassy weeds (81% – 100%). Most of the herbicidetreatments significantly increased alfalfa fresh and dry matter yields incomparison with the weedy check